Improving the Emotional Intelligence of Learners in Primary Schools: What is the Teacher's Attitude? - Yuntira, Yuntira; Indria, Anita; Asril, Zainal; Nafian, Zidni Ilman (Ahlussunnah: Journal of Islamic Education, 2024)
This problem stems from students from Integrated Islamic Elementary Schools, who are expected to have better emotional states than students from other public elementary schools. However, researchers found students with negative emotional states, such as socializing with friends, talking to friends, being assertive toward teachers, and not paying attention to lessons, not accepting their own mistakes, being unwilling to accept others' opinions, and being overly sensitive. Therefore, researchers wanted to investigate the causes of these emotional states in students. This research using field research methods through a descriptive qualitative approach, with techniques snowball sampling. Data collection techniques using observation, interviews and documentation. This study resulted in teacher efforts in increasing students' self-awareness at Insan Kamil Integrated Islamic Elementary School by accustoming children to good behavior or morals, teaching children prayers and knowing Allah as the creator of the universe, giving advice in small forums, and getting used to being polite, appreciating and respecting others. Teachers' efforts in increasing student motivation by means of high motivation are by giving numbers, medium motivation by giving questions and assignments and low motivation by giving punishment. Teachers' efforts in increasing student empathy by giving advice about caring for fellow friends, giving children opportunities to be active and inviting children to contemplate nature.